Early postoperative management of common bile duct injury - Cantileno, Pablo; Bello, Lucia; Lapi, Silvana; Olivera, Eduardo; Rodríguez, Gustavo (Cirugía del Uruguay, 2026)
The Injury of the Bile duct after cholecystectomy determines a serious medical problem that affects the patients as well as the acting medical team with the risk of legal litigation. Most injuries are diagnosed in the immediate postoperative period. The time it takes between the injury and the diagnosis impacts on the results of definitive repair, as well as the morbidity and mortality of the patient. Thus, the less time between the injury and the diagnosis, impact positively in the results of the definitive treatment, quality of life and prognosis in terms of morbility and mortality of the patient. The aim of this article was to analyze the early postoperative management of the bile duct injuries. Will be analyzed in relation whit 2 clinical cases treated in our Assistant Unit of surgical clinic.